Do Resident and Non-Resident Northern Bobwhite Hunters Self-Regulate Harvest Based on Population Size? - Christopher K. Williams; Roger D. Applegate (National Quail Symposium Proceedings, 2017)
A variety of factors influence the relative strength of additive and compensatory mortality of harvest on northern bobwhite (Colinus virginianus) including covey dynamics, habitat fragmentation, and timing of harvest. State wildlife agencies have long believed regulations could be liberal because hunters will self-regulate effort when populations decrease. A confounding observation is that with lower population abundances, hunter skill and harvest rate increases because the more novice hunters do not participate. This raises the question whether non-resident small game hunters could have a larger impact at lower population levels if they have (1) more money to dedicate to out of state licenses and travel/lodging, and (2) time to dedicate to the hunting experience? We examined long-term bobwhite population and harvest data from Kansas (1966–1999) to learn if self-regulation differed between resident and non-resident small game hunters. The number of resident and non-resident small game hunters was related to their respective harvest of northern bobwhites. Decreasing October population index was associated with a decline in the number of resident bobwhite hunter days and harvest. Conversely, increasing numbers of non-resident hunters participated in the hunting season with higher hunter efficiency and a larger harvest at lower October population index levels. Total relative harvest decreased overwinter (Oct–Jan) survival. The Kansas resident bobwhite harvest is probably self-regulatory but non-resident harvest is not. Future harvest regulations should consider the impact of non-resident harvest.
Keywords: Colinus virginianus; hunting; nonresident; northern bobwhite; resident; self-regulation